The Correlation Between Students` Critical Thinking and Speaking Skill in English Class at Diploma 4 of The Health Promotion Study Program - Dewi, Indri Puspita; Aisyah, Noor; Azhimia, Faida; Rahmadani, Nur (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2024)
English is a crucial medium of communication, with fluency in four language skills: listening, speaking, reading, and writing. Speaking is one of the most challenging skills, as it allows students to engage in conversations, express meaning, and express opinions. Thinking is a key factor in developing speaking abilities, as it helps individuals solve issues, make decisions, and achieve goals. This research aimed to measure the correlation between students' critical thinking and their speaking skills. A quantitative study of 14 first-semester students of the Diploma 4 Health Promotion study program at Sari Mulia University found a weak correlation (rho coefficient 0.209, sig. score 0.494). The results reject the alternative hypothesis (Ha), indicating that there is no significant correlation between students' critical thinking and speaking ability, confirming the null hypothesis (Ho), is accepted.